UTILIZATION OF HOUSEHOLD WASTE IN PEMATANG SULUR VILLAGE: PEMANFAATAN SAMPAH RUMAH TANGGA DI KELURAHAN PEMATANG SULUR - Erris Erris; Krisdiyanta Krisdiyanta (Yayasan Education and Social Center, 2022)
Waste management is a systematic, thorough, and sustainable activity that includes reducing and handling waste. Activities in waste management include waste generation control, waste collection, transportation, processing, and final disposal (Law No. 18 of 2008 concerning Waste Management). The purpose of community service is to increase the knowledge of the Chairman of the Neighboring Pillars about the processing of household waste in Pematang Sulur Village, Jambi City, forming a Household Waste Utilization Activist in Pematang Sulur Village, Jambi City. Pematang Sulur Village is a village located in Jambi City. The heterogeneous community environmental conditions, in general, do not pay attention to the environment identical to settlements that still make it possible to make piles of garbage in the yard of the house. The behavior of people who care less about the environment can be seen in the garbage that is thrown away and scattered in residential areas. If you look at Pematang Sulur Village, whose community characteristics are compound/heterogeneous, waste management is necessary along with the development and population growth; some residents may not realize the meaning of environmental cleanliness. In addition, the existence is very vulnerable to water pollution, siltation, and narrowing of the river, which also hampers groundwater processes if some of the existing communities throw their waste directly into the river. There is much plastic waste that the soil cannot decompose, which will result in the accumulation of waste and waste. Community service concludes that there is a significant difference between knowledge before and after education or counseling on household waste processing in Pematang Sulur Village, Jambi City, the formation of the Activists for the Utilization of household waste in Pematang Sulur Village, Jambi City.